Digital Autoethnography & Connected Intelligence: Two Qualitative Practice-Based Teaching Methods for the Digital Humanities - Calzati, Stefano (Umanistica Digitale, 2020)
In higher education we witness a unique conjuncture: on the one hand, students who attend academic courses are the first generation to have fully grown in a digitalized world; on the other hand, teachers, while having grown and studied in a still largely analogue world, have witnessed the evolution of today’s techno-society since its infancy. By connecting the field of the Digital Humanities with education, this article discusses the conception, design and results of two practice-based teaching experiences which were aimed at exploring the tensions embedded in our daily use of digital technologies, as well as in today’s techno-society as a whole. The first one is a “digital autoethnography” developed at the City University of Hong Kong; the second one refers to the course “Anthropology of Communication” – co-delivered at Politecnico of Milan – which adopted a “connected intelligence” approach to urge students to reflect on tomorrow’s techno-society in a collaborative way. While the first experience was chiefly a self-reflexive study on the impact of social media on the individual, the second one mapped the main criticalities of techno-society as a whole, according to seven macro-themes, and asked students to elaborate possible solutions. Both courses considered students as active learners/users, insofar as they at the forefront of today digital revolution, but also the subjects most in need of critical tools to face it.